“Measuring Poverty”: Discussion - Kremer, Michael (The Review of Economics and Statistics, 2005)
February 01 2005 “Measuring Poverty”: Discussion Michael Kremer Michael Kremer Harvard University Search for other works by this author on: This Site Google Scholar Author and Article Information Michael Kremer Harvard University Received: May 26 2004 Accepted: July 28 2004 Online ISSN: 1530-9142 Print ISSN: 0034-6535 © 2005 President and Fellows of Harvard College and the Massachusetts Institute of Technology2005 The Review of Economics and Statistics (2005) 87 (1): 23–25. https://doi.org/10.1162/0034653053327630 Article history Received: May 26 2004 Accepted: July 28 2004 Cite Icon Cite Permissions Share Icon Share Facebook Twitter LinkedIn Email Views Icon Views Article contents Figures & tables Video Audio Supplementary Data Peer Review Search Site Citation Michael Kremer; “Measuring Poverty”: Discussion. The Review of Economics and Statistics 2005; 87 (1): 23–25. doi: https://doi.org/10.1162/0034653053327630 Download citation file: Ris (Zotero) Reference Manager EasyBib Bookends Mendeley Papers EndNote RefWorks BibTex toolbar search Search Dropdown Menu toolbar search search input Search input auto suggest filter your search All ContentAll JournalsThe Review of Economics and Statistics Search Advanced Search This content is only available as a PDF. © 2005 President and Fellows of Harvard College and the Massachusetts Institute of Technology2005 Article PDF first page preview Close Modal You do not currently have access to this content.